Prevalence of β-Lactamase-Encoding Genes among Enterobacteriaceae Bacteremia Isolates Collected in 26 U.S. Hospitals: Report from the SENTRY Antimicrobial Surveillance Program (2010) - Mariana Castanheira; Sarah E. Farrell; Lalitagauri M. Deshpande; Rodrigo E. Mendes; Ronald N. Jones (2013)
Enterobacteriaceae bacteremia isolates (n = 195; 6.4% overall) collected from 26 U.S. hospitals located in 20 states were screened for various β-lactamase classes. A total of 175 isolates carried one to eight acquired β-lactamase genes of 44 types that were detected in 55 combinations. Eighty-five (43.6%) strains carried blaCTX-M, and blaCTX-M-15 was the most prevalent (33.8%). Genes encoding OXA-1/30 (often associated with blaCTX-M-15), CMY-2, SHV extended-spectrum β-lactamase (ESBLs), and TEM-1 were also prevalent. Among 33 carbapenem-resistant strains, 28 carried blaKPC-2 or blaKPC-3 (17 and 11 strains, respectively), and those were recovered mostly in the New York City area (16 strains) and Houston, TX (9 strains). Fourteen new SHV variants were identified among Klebsiella pneumoniae isolates carrying one or multiple SHV alleles, three carrying G238S and/or E240K amino acid alterations that confer ESBL activity. Only two of eight K. oxytoca isolates carried acquired β-lactamases, but most had mutations on the blaOXY promoter region, and three new OXY-encoding genes were characterized. Concordance between a commercial nucleic acid-based microarray (Check-MDR CT101) and reference methods was noted for 105/109 (97.2%) strains. Thirty-two strains having genes that are not targeted by the commercial system were detected (OXA ESBLs, PER, PSE, or intrinsic genes). Overall, a great variety of enzymes were observed, with numerous strains carrying multiple genes. Rates of CTX-M-producing strains appear to be increasing in U.S. hospitals (26.6% in 2007 to 43.8% for 2010) participating in the SENTRY Program. Furthermore, the Check-Points system seems to be a reliable, robust, and user-friendly assay for detection of enzyme-mediated resistance.